Experimental Studies of Latissimus Dorsi Detrusor Myoplasty for Bladder Acontractility: A Systematic Review. Issue 3 (July 2021) - Forte, Antonio J.; Boczar, Daniel; Huayllani, Maria T.; Moore, Pamela A.; Moran, Steven L.; Okanlami, Oluwaferanmi O.; Ninković, Milomir; Broer, Peter N.
Abstract : Current therapies that allow patients with bladder acontractility to void are limited. The standard therapy is clean intermittent catheterization. Latissimus dorsi detrusor myoplasty (LDDM) has been shown to provide functional contraction and allow patients with bladder acontractility to void voluntarily. Our goal was to summarize experimental studies of LDDM. We hypothesized that experimental studies would show that latissimus dorsi muscle (LDM) flaps for detrusor myoplasty have superior outcomes when compared with other types of flaps. On January 17, 2020, we conducted a systematic review of the PubMed/MEDLINE, Cochrane Clinical Answers, Cochrane Central Register of Controlled Trials, and EMBASE databases, without time frame limitations, to identify articles on the use of LDDM. We excluded studies that investigated other treatments. Of 54 articles identified by the search, three fulfilled the eligibility criteria. A total of 24 dogs underwent procedures and were evaluated with a maximum follow-up of 9 months. Three types of procedures were performed: LDM in situ reconfiguration, LDM myoplasty, and augmentation cystoplasty after supratrigonal cystectomy. Electrical stimulation, cystography, urodynamic and hydrodynamic measurements, and microscopic examinations were performed. Innervated LDM flaps transferred to the bladder were able to contract and promote voiding in response to electrical stimulation. Experimental studies have shown the feasibility of LDDM in canine models. Although no comparison groups were included, innervated LDM flap transferred to the bladder showed promising results regarding contraction capable of voiding.